2017
DOI: 10.7196/samj.2017.v108i1.11090
|View full text |Cite
|
Sign up to set email alerts
|

Keeping our heads above water: A systematic review of fatal drowning in South Africa

Abstract: This review suggests that SA drowning prevention initiatives are currently confined to the early stages of an effective injury prevention strategy. The distribution of mortality across age groups and drowning location differs substantially between urban centres and provinces. There is therefore a need for detailed drowning surveillance to monitor national trends and identify risk factors in all SA communities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 17 publications
(72 reference statements)
4
8
0
Order By: Relevance
“…In many African countries, cases go unreported and the lack of an injury surveillance system as seen in many LMIC also contributes to the limited data [65]. This is consistent with the findings of two recent systematic reviews describing the burden of drowning in South Africa and Tanzania [16,17]. Saunders et al and Sarrassat et al, reported that strengthening the existing surveillance systems or establishing new ones are needed for consistent and detailed drowning surveillance [16,17].…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…In many African countries, cases go unreported and the lack of an injury surveillance system as seen in many LMIC also contributes to the limited data [65]. This is consistent with the findings of two recent systematic reviews describing the burden of drowning in South Africa and Tanzania [16,17]. Saunders et al and Sarrassat et al, reported that strengthening the existing surveillance systems or establishing new ones are needed for consistent and detailed drowning surveillance [16,17].…”
Section: Discussionsupporting
confidence: 75%
“…Currently, there is no systematic review investigating drowning in Africa. Only three recent reviews on drowning in low- and middle-income countries, drowning in South Africa and Tanzania respectively have been published [8,16,17]. Therefore, it is imperative to understand the epidemiology, risk factors and current prevention strategies in Africa to direct policies for the prevention of drowning in Africa.…”
Section: Introductionmentioning
confidence: 99%
“…The limited peer-reviewed studies from Africa also highlight the need for a greater focus on drowning in Africa, especially considering that 11 of the 16 articles were from South Africa 5. Another review of drowning in South Africa showed large heterogeneity in drowning across the country, a potential challenge for estimating the number of drowning deaths in Africa 13…”
Section: Discussionmentioning
confidence: 99%
“… 5 Another review of drowning in South Africa showed large heterogeneity in drowning across the country, a potential challenge for estimating the number of drowning deaths in Africa. 13 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation